Expression of Genetic Polymorphism of TMPRSS2 Gene (Rs12329760) in Different Ethnicities of Prostate Cancer Patients: A Case Control Study - Sadiq, Saadia; Rahim, Amena; Afzal, Muhammad; Ikram, Sahar; Kohistani, Tehseen Ashraf; Munir, Farzana (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency and clinical relevance of the TMPRSS2 gene polymorphism (rs12329760) in prostate cancer patients of different ethnicities. Study Design: Case-control study. Place and Duration of Study: Department of Biochemistry, Islamic International Medical College, Rawalpindi, Surgical unit of Railway General Hospital, Rawalpindi, and Urology Department of National Institute of Rehabilitative Medicine, Islamabad, Pakistan, from Oct 21 to Sep 22. Methodology: There were 200 participants included in this study, with 100 cases of prostate cancer and 100 age-matched controls. Blood samples were collected from the outpatient department (OPD) and ward. The Chelex method was used for DNA extraction. Tetra-ARMS Polymerase chain reaction was carried out to determine the respective allelic frequencies of the TMPRSS2 gene polymorphism (rs12329760) using specific primers. Results: CT and TT genotypes of TMPRSS2 gene polymorphism (rs12329760) showed a significant association in prostate cancer patients (p-value˂0.001). T-allele of TMPRSS2 gene polymorphism (rs12329760) also showed a significant association in prostate cancer patients (p-value<0.001). Significant association was also found in Pathans with CT and TT genotype of TMPRSS2 gene polymorphism (rs12329760) with p-values of 0.01 and 0.004. Punjabis also showed a significant association with CT genotype of TMPRSS2 gene polymorphism (rs12329760) with a p-value of 0.004. Conclusion: TMPRSS2 gene polymorphism (rs12329760) is strongly linked to a higher risk of developing prostate cancer in Pathans and Punjabis within the Pakistani population.